2008
DOI: 10.1002/ddrr.15
|View full text |Cite
|
Sign up to set email alerts
|

The nervous system and gastrointestinal function

Abstract: The enteric nervous system is an integrative brain with collection of neurons in the gastrointestinal tract which is capable of functioning independently of the central nervous system (CNS). The enteric nervous system modulates motility, secretions, microcirculation, immune and inflammatory responses of the gastrointestinal tract. Dysphagia, feeding intolerance, gastroesophageal reflux, abdominal pain, and constipation are few of the medical problems frequently encountered in children with developmental disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 104 publications
1
26
0
Order By: Relevance
“…In the present study, the gaps and contradictions in the Residents' knowledge of such a common symptom are striking, particularly with respect to its multifactorial causes (Amendola et al, 2003;Farnam, et al, 2009;Motta et al, 2010;Poenaru et al, 1997;Silva, 2009;van den Berg et al, 2006), as well as the importance of multidisciplinary treatment in cases of FC, as already established in the literature (Altaf & Sood, 2008;Amendola et al, 2003;Nehra et al, 2000;Poenaru et al, 1997). In a systematic review, prevalence rates of constipation in 34 groups of different populations in Europe and Oceania ranged from 0.7% in a pediatric population in Italy to 81.0% in a population of elderly, hospitalized male patients.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, the gaps and contradictions in the Residents' knowledge of such a common symptom are striking, particularly with respect to its multifactorial causes (Amendola et al, 2003;Farnam, et al, 2009;Motta et al, 2010;Poenaru et al, 1997;Silva, 2009;van den Berg et al, 2006), as well as the importance of multidisciplinary treatment in cases of FC, as already established in the literature (Altaf & Sood, 2008;Amendola et al, 2003;Nehra et al, 2000;Poenaru et al, 1997). In a systematic review, prevalence rates of constipation in 34 groups of different populations in Europe and Oceania ranged from 0.7% in a pediatric population in Italy to 81.0% in a population of elderly, hospitalized male patients.…”
Section: Discussionsupporting
confidence: 49%
“…These findings highlight the difficulty of the majority of pediatrics Residents in diagnosing FC, a fundamental step in defining treatment. None, for example, mentioned normal or slow colonic transit as a factor in children with FC (Altaf et al, 2008;van den Berg et al, 2010), showing an obvious need to provide greater in-depth information on these issues.…”
Section: Discussionmentioning
confidence: 99%
“…1 A focus on recent population-based research, 26 however, indicates that the evidence supporting an association of GI disturbances with ASD is not consistent (eTable 1 in the Supplement). Reports 7–9 of elevated GI dysfunction in individuals with neurodevelopmental disorders other than autism raise the added possibility that GI findings may not be specific to ASD. To our knowledge, there have been no population-based studies of prospectively reported GI symptoms and disorders that compare children with ASD with children with typical development (TD) and developmental delay (DD).…”
mentioning
confidence: 99%
“…However, it can lead to changes that are to some extent, irreversible 5,8,14. From this study, it can be considered that jejunal interposition is effective and less complicated than colon interposition. 2,3,7,8 Intestinal interpositions are relevant in several operations on the digestive tract. However, they are not exempt from immediate and long-term complications, and may cause death.…”
Section: Anatomopathological Examinationmentioning
confidence: 99%